Similar outcomes of allogeneic hematopoietic cell transplantation from unrelated donor and umbilical cord blood vs. sibling donor for pediatric acute myeloid leukemia: Multicenter experience in China. (22nd April 2015) - Tang, Xiangfeng; Chen, Jing; Fang, Jianpei; Sun, Xin; Qin, Mao Quan; Li, Junhui; Zhu, Yiping; Luan, Zuo
Abstract In a multicenter study, we have conducted a retrospective study on 73 pediatric AML patients who were primary refractory or in greater than CR1 and investigated MSD (or MMSD) (n = 20), URD (n = 23), and UCB (n = 30) HCT between January 1998 and October 2009. The median day to neutrophil engraftment was similar in all groups. The median day to platelet engraftment was longer in the UCB group. The number of HLA mismatch was higher in the UCB group (p = 0.034); however, the cumulative incidence of grade III–IV aGVHD was not different among all groups (p = 0.125); furthermore, cGVHD was lower in the UCB group (p = 0.078). The risk of relapse did not differ among all groups (RR = 1.28, p = 0.125), but the patients of MSD (or MMSD) grafts had a trend of higher risk recurrence. Sixty‐two patients survived with a median follow‐up of 58.2 months. Five‐yr LFS was 73.1%, 59.8%, and 59.6% for URD, UCB, and MSD (or MMDS), respectively (p = 0.426). Five‐yr LFS in CR1 was 68.9%, with a significantly better result compared to 41.7% in CR2 (p = 0.025). Our comparisons suggest that pediatric AML patients receiving UCB had a higher early TRM, a lower cGVHD rate, and a similar long‐term survival. The outcome of URD and UCB is comparable to that of a suitable sibling for pediatric AML.